Good metabolic control is associated with decreased circulating factor VIIa– antithrombin complexes in type 2 diabetes: a cross-sectional study - Gastoł, Joanna; Paszek, Elżbieta; Bryk-Wiązania, Agata; Matejko, Bartłomiej; Undas, Anetta (Cardiovascular diabetology, 2024)
Background Diabetes is associated with a prothrombotic state that contributes to cardiovascular (CV) events in type 2 diabetes (T2DM). Activated factor VII (FVIIa)– antithrombin (AT) complexes are indicative of tissue factor (TF) exposure and have been associated with thromboembolic risk in coronary artery disease. To our knowledge there have been no reports on FVIIa-AT complexes in T2DM, therefore we assessed factors that determine FVIIa-AT complexes in this disease and the impact of higher complexes on a prothrombotic state. Methods In 108 T2DM patients (mean age 63.8 years, 52.8% men, median HbA1c of 6.9 [interquartile range 6.1–8.2] %) and 83 age- and sex-matched non-diabetic subjects, we measured FVIIa-AT complexes. Metabolic control of T2DM involved fasting glucose, glycated hemoglobin (HbA1c), albumin/creatinine ratio (ACR), and lipid levels. To characterize a prothrombotic state, we determined thrombin generation parameters, fibrinolysis markers, and plasma fibrin clot properties. Results FVII-AT complexes in T2DM patients were similar to controls (73.6 [59.4–91.7] vs. 79.6 [59.2–97.1]pM, respectively, p = 0.30). The T2DM patients with FVIIa-AT in the top vs. the bottom quartile had a larger prevalence of active smoking and insulin use, along with higher fasting glucose (+ 36.4%), HbA1c (+ 27.4%), ACR (+ 72.8%), total cholesterol (+ 34.5%), and LDL-cholesterol (+ 80%). FVIIa-AT complexes showed no associations with in vitro thrombin generation potential, plasma fibrin clot properties, or fibrinolysis variables. On multivariable analysis HbA1c, ACR, and total cholesterol remained independently associated with FVIIa-AT complexes in T2DM. Conclusions This is the first study to show that in T2DM higher FVIIa-AT complexes are associated with markers of dyslipidemia and glycemia control, indicating that TF-induced coagulation activation could be suppressed by achieving treatment targets. Graphical abstract